Apigenin as an emerging hepatoprotective agent: current status and future perspectives - Wang, Cheng; Feng, Xiaoli; Li, Wen; Chen, Li; Wang, Xinming; Lan, Yimiao; Tang, Rong; Jiang, Ting; Zheng, Lingli; Liu, Gang (Frontiers in Pharmacology, 2024)
Apigenin (C15H10O5, API) is a natural flavonoid widely found in vegetables, fruits, and plants such as celery, oranges, and chamomile. In recent years, API has attracted considerable attention as a dietary supplement due to its low toxicity, non-mutagenic properties and remarkable therapeutic efficacy in various diseases. In particular, evidence from a large number of preclinical studies suggests that API has promising effects in the prevention and treatment of a variety of liver diseases, including multifactorial liver injury, non-alcoholic fatty liver disease/non-alcoholic steatohepatitis, liver fibrosis and liver cancer. This paper provides a comprehensive review of the progress of research into the therapeutic applications of API in liver diseases as of August 2024, based on literature retrieved from databases such as Web of Science, PubMed, CNKI, Google Scholar and ScienceDirect. The hepatoprotective effects of API involve multiple molecular mechanisms, including inhibition of inflammation, alleviation of hepatic oxidative stress, amelioration of insulin resistance, promotion of fatty acid oxidation, inhibition of liver cancer cell proliferation and differentiation, and induction of tumour cell apoptosis. More importantly, signaling pathways such as Nrf2, NF-κB, PI3K/Akt/mTOR, NLRP3, Wnt/β-catenin, TGF-β1/Smad3, AMPK/SREBP, PPARα/γ, MAPKs, and Caspases are identified as key targets through which API exerts its beneficial effects in various liver diseases. Studies on its toxicity and pharmacokinetics indicate that API has low toxicity, is slowly metabolized and excreted in vivo, and has low oral bioavailability. In addition, the paper summarises and discusses the sources, physicochemical properties, new dosage forms, and current challenges and opportunities of API, with the aim of providing direction and rationale for the further development and clinical application of API in the food, pharmaceutical and nutraceutical fields.